Organophosphorus Chemistry: A New Perspective (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Printed Edition of the Special Issue "Organophosphorus Chemistry: A New Perspective" takes the reader on a journey through the chemistry of organophosphorus compounds. It contains seven original research articles and three reviews covering aspects of recent advances in the synthesis, transformation, and properties of P-compounds.